Clinical and Neuroimaging Features in Two Children with Mutations in the Mitochondrial ND5 Gene - Sonam, Kothari; Bindu, P. S.; Taly, Arun B.; Govindaraju, Chikkanna; Gayathri, Narayanappa; Arvinda, Hanumanthapura R.; Nagappa, Madhu; Sinha, Sanjib; Khan, Nahid Akthar; Govindaraj, Periyasamy; Thangaraj, Kumarasamy (Neuropediatrics, 2015)
Mutations in the mitochondrial-encoded nicotinamide adenine dinucleotide dehydrogenase 5 gene (MT-ND5) has been implicated as an important genetic cause of childhood mitochondrial encephalomyopathies. This study reports the clinical and magnetic resonance imaging findings in two pediatric patients with mutations in the ND5 gene of mitochondrial DNA. The 8-month-old boy with m.13513 G > A mutation presented with infantile basal ganglia stroke syndrome secondary to mineralizing angiopathy. The 7-year-old girl with the m.13514A > G mutation had episodic regression, progressive ataxia, optic atrophy, and hyperactivity. Magnetic resonance imaging of the brain showed bilateral symmetrical signal intensity changes in the thalamus, tectal plate, and inferior olivary nucleus, which subsided on follow-up image. Both the patients had a stable course. Familiarity with the various phenotypic and magnetic resonance imaging findings and the clinical course in childhood mitochondrial encephalomyopathies may help the physician in targeted metabolic–genetic testing and prognostication.
Keywords: mitochondrial encephalmyopathy; ND5 mutation; m.13513G > A; m.13514A > G Mineralizing angiopathy